2017
DOI: 10.1055/s-0037-1599204
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the Knee: Common Pathology Excluding Extensor Mechanism

Abstract: Ultrasound can be used to diagnose many types of pathology and guide various diagnostic or therapeutic procedures. The most common applications for musculoskeletal ultrasound of the knee include evaluation of the joint recesses, the extensor mechanism, and bursae including Baker's cyst. However, a role exists for ultrasound in the evaluation of cartilage, other tendons, ligaments, peripheral nerves, osseous structures, and vasculature. This article reviews common pathologies of these structures as seen with ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 80 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…Dynamic US examination of the medial structures of the knee has been proven to be a suitable method to describe medial joint space width [8, 12, 21, 25, 32]. It has been shown that the US examination is a good alternative to valgus stress radiographs, as it is radiation‐free [11, 25], easy to learn [8], cheap, and allows for a dynamic assessment of the medial joint space [8, 12]. Combined with a fixation device, standardized and reproducible measurements of the medial joint width [8] are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic US examination of the medial structures of the knee has been proven to be a suitable method to describe medial joint space width [8, 12, 21, 25, 32]. It has been shown that the US examination is a good alternative to valgus stress radiographs, as it is radiation‐free [11, 25], easy to learn [8], cheap, and allows for a dynamic assessment of the medial joint space [8, 12]. Combined with a fixation device, standardized and reproducible measurements of the medial joint width [8] are possible.…”
Section: Discussionmentioning
confidence: 99%
“…US is an excellent imaging modality for the evaluation of superficial soft tissue structures. 21 , 22 Direct correlation with the site of pain and comparison with the controlateral normal side are some of the advantages of US. For the evaluation of medial structures, it is important to identify the medial epicondyle as a femoral bony landmark.…”
Section: Imagingmentioning
confidence: 99%
“…For the evaluation of medial structures, it is important to identify the medial epicondyle as a femoral bony landmark. 21 The examination of the medial compartment is conducted at 30° of flexion. Voluntary external rotation facilitates visualization of the medial knee side.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…For ankle effusion, planes in the longitudinal and transversal axis of the talocrural joint were assessed. (Gaulrapp;Jacobson, Ruangchaijatuporn, Khoury, & Magerkurth, 2017;Kane, Balint, & Sturrock, 2003;Terslev et al, 2012) The effusion was graded 0-3 according to Hartung et al -an ultrasound score originally developed for patients with rheumatoid arthritis, which has also been used to evaluate other populations, including marathon runners. (Hartung et al, 2012;Proft et al, 2016).…”
Section: Sonographymentioning
confidence: 99%